IgA With altered carbohydrate structure as a tumor-associated marker in serum of cancer patients - Henslee, Jerry G.; Rittenhouse, Harry G.; Matias, Matthew S.; Michael Hass, G.; Schenck, Jay R.; Tomita, Joseph T. (Journal of clinical laboratory analysis, 1988)
Serum IgA1 contains O‐linked carbohydrate structures, whereas other immuno‐globulins contain only N‐linked structures. An assay was developed which detects IgA1 by measuring the DGalβ(1–3) DGalNAc structures O‐linked to the IgA1 hinge region. Fifty percent of the serum specimens from cancer patients tested were elevated compared to 1% of the total normal serum specimens tested by this assay. The assay combines antibody (anti‐human IgA) and lectin and measures the DGalβ(1–3)DGalNAc structure in the IgA1 molecule accessible to lectin binding. Three lectins were compared–the lectins from Bauhinia purpurea alba, Maclura pomifera, and peanut agglutinin (PNA). PNA in the assay discriminated best between serum specimens from normal subjects and cancer patients and was chosen as the lectin component in the assay. The anti‐IgA‐PNA enzyme immunoassay was evaluated in a retrospective study of cancer patients. A panel of 845 serum specimens was tested and the results analyzed at three cutoff R values. The R value of a specimen is the ratio of the assay absorbance obtained for that test specimen with respect to the assay absorbance obtained for a pool of normal human sera. At a cutoff R value of 2.38, 1% normals and 26% benigns were elevated. The following cancer specimens had elevated R values: 52% lung, 60% colon, 43% head and neck, 35% breast, 64% kidney, 38% bladder, 43% prostate, 8% ovarian, and 67% pancreas. Further testing showed a significant percentage of serum specimens from patients with cirrhosis, pancreatitis, or ulcerative colitis also had elevated R values. No correlation of this assay was observed with CEA levels. The results suggest that the carbohydrate structure of serum IgA1 is altered by malignancies and that measurement of this altered IgA may supplement CEA testing.